REVVING UP SALES: THE IMPACT OF BRAND IMAGE AND PRICE ON BUYING INTEREST FOR HONDA PCX IN BANDUNG - Ryan Kurniawan; Rizqi Yakhusna; Dinda Trie Munizah (PT. Altin Riset Publishing, 2025)
This research aims to analyze the influence of Brand Image and Price on Buying Interest (Case Study of Honda PCX Motorcycle Users in Bandung City). Competition between motorbike brands in Indonesia continues to occur, including the Honda and Yamaha brands. Each brand has advantages that can be emphasized to consumers, so that consumers are interested in making purchases from the brands they offer. However, the Yamaha motorbike brand (Nmax) has proven to be superior in sales compared to the Honda motorbike brand (PCX) in 2024. This research method utilizes Google facilities which are often used by everyone, namely online Google forms with a sample of 100 respondents who use Honda PCX motorbikes. The research results show that brand image and price have a significant effect on consumer buying interest. A strong brand image and competitive prices increase consumer buying interest. This research provides implications for companies to maintain and improve the quality of their brand image and adjust prices to consumer needs.